Effects of Chronic Antihypertensives on Vasopressor Dosing in Septic Shock. Issue 1 (January 2018) - DeMott, Joshua M.; Patel, Gourang; Lat, Ishaq
Background: In septic shock, chronic antihypertensive medications are held acutely. Vasopressors are often required to maintain blood pressure. The effect of chronic exposure to antihypertensive therapies on vasopressor dosing in septic shock is not known.Objective: To determine the effects of chronic exposure to antihypertensive therapies, specifically β-blockers and angiotensin-converting enzyme (ACE) inhibitors, on cumulative vasopressor dosing in septic shock.Methods: This was a retrospective cohort review, with data collected from routine care. Patients admitted to the medical intensive care unit with septic shock and vasopressor use were included and divided into 4 groups based on chronic medication use: (1) no β-blocker or ACE inhibitor, (2) β-blocker only, (3) ACE inhibitor only, and (4) β-blocker and ACE inhibitor. Cumulative vasopressor dose at 48 hours was assessed. Demographics, comorbid conditions, suspected site of infection, disease severity, mortality, and concomitant therapies were evaluated between groups.Results: A total of 133 patients with septic shock treated with vasopressors were included. No difference in cumulative vasopressor dose at 48 hours was detected between the 4 groups, respectively (median norepinephrine milligram equivalents [interquartile range (IQR)]: no β-blocker or ACE inhibitor, 13.7 mg [6.0-35.7]; β-blocker only, 13.1 mg [5.4-23.9]; ACE inhibitor only, 13.2 mg [1.2-36.7]; β-blocker and ACE inhibitor, 11.3 mg [4.7-42.9]; P = 0.669). Total time on vasopressors differed between groups (median hours [IQR]: no β-blocker or ACE inhibitor, 30h [17-60]; β-blocker only, 24h [10-69]; ACE inhibitor only, 19h [6-25]; β-blocker and ACE inhibitor, 30h [15-58]; P = 0.031). Comorbid conditions, suspected infection sites, disease severity, mortality, and concomitant therapies were similar.Conclusions: Chronic β-blocker, ACE inhibitor use, or the combination of both did not affect cumulative vasopressor dose at 48 hours in septic shock. However, prior-to-admission medications may affect total time of vasopressor use.